The application of machine learning to imaging in hematological oncology: A scoping review - Kotsyfakis, Stylianos; Iliaki-Giannakoudaki, Evangelia; Anagnostopoulos, Antonios; Papadokostaki, Eleni; Giannakoudakis, Konstantinos; Goumenakis, Michail; Kotsyfakis, Michail (Frontiers in Oncology, 2022)
Here we conducted a scoping review to: (i) establish which machine learning (ML) methods have been applied to hematological malignancy imaging; (ii) establish how ML is being applied to hematological cancer radiology; and (iii) identify addressable research gaps. The review was conducted according to PRISMA-ScR guidelines. The inclusion criteria were: (i) pediatric and adult patients with suspected or confirmed hematological malignancy undergoing imaging (population); (ii) any study using ML techniques to derive models using radiological images to apply to the clinical management of these patients (concept); and (iii) original research articles conducted in any setting globally (context). Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) criteria were used to assess diagnostic and segmentation studies, while the Newcastle-Ottawa scale was used to assess the quality of observational studies. Of 53 eligible studies, 33 applied diverse ML techniques to diagnose hematological malignancies or to differentiate them from other diseases, especially discriminating gliomas from primary central nervous system lymphomas (n=18); 11 applied ML to segmentation tasks; while nine applied ML to prognostication or predicting therapeutic responses, especially for diffuse large B cell lymphoma. All studies reported discrimination statistics, but no study calculated calibration statistics. Every diagnostic/segmentation study had a high risk of bias due to their case-control design; many studies failed to provide adequate details of the reference standard; and only a few studies used independent validation. To deliver validated ML-based models to radiologists managing hematological malignancies, future studies should: (i) adhere to standardized, high-quality reporting guidelines such as the Checklist for Artificial Intelligence in Medical Imaging (CLAIM); (ii) validate models in independent cohorts; (ii) standardize volume segmentation methods for segmentation tasks; (iv) establish comprehensive prospective studies that include different tumor grades, comparisons with radiologists, optimal imaging modalities, sequences, and planes; (v) include side-by-side comparisons of different methods; and (vi) include low- and middle-income countries in multi-centric studies to enhance generalizability and reduce inequity.